2017
DOI: 10.1088/1757-899x/229/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanate-modified Nano-SiO2 and Corresponding Process Optimization

Abstract: Abstract. Nano-SiO 2 is hydrophilic, and the surface of nano-SiO 2 should be modified to improve its dispersion in a polymer matrix. Here, triallyl isocyanurate was selected to modify the surface of the nano-SiO 2 powders. Because the reaction between isocyanate groups (-NCO) and hydroxyl groups (-OH) on surface of the nano-SiO 2 does not need any pre-treatment, one single and simple step can facilitate the graft. By optimizing the specific modification process via orthogonal experiments, optimal processing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The absorption peak was observed at 1690 cm −1 in TI–NS, which indicates fewer hydroxyl groups whereas the peak corresponding to 1456 cm −1 revealed the presence of CN absorption. Ye et al have reported similar findings 18 …”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The absorption peak was observed at 1690 cm −1 in TI–NS, which indicates fewer hydroxyl groups whereas the peak corresponding to 1456 cm −1 revealed the presence of CN absorption. Ye et al have reported similar findings 18 …”
Section: Resultssupporting
confidence: 65%
“…Ye et al have reported similar findings. 18 As observed from Figure 1C, the FTIR spectra of the CP showed NH stretching at 3366 cm À1 , while in the case of PU…”
Section: Fourier Transform Infraredmentioning
confidence: 64%
See 3 more Smart Citations